Analisis Framing Pemilu 2024 Dalam Film Dokumenter “Dirty Vote” - Aisyah, Elinawati; Suratnoaji, Catur (Fakultas Ilmu Sosial dan Ilmu Poliitik Universitas Ichsan Gorontalo, 2025)
This study analyzes media framing of the 2024 election fraud issue in Indonesia through the documentary film Dirty Vote. The method used is framing analysis with a descriptive qualitative approach. Data analysis in this study applies the model of Zhongdang Pan and Gerald M. Kosicki, which includes four structures: syntax, script, thematic, and rhetoric. Results indicate that Dirty Vote frames election fraud as a significant threat to democracy, portraying manipulation by political elites as a structured strategy. The syntactic structure highlights the role of political elites, the script presents manipulation through the appointment of non-neutral officials and the politicization of social aid, the thematic structure shows threats to justice, and the rhetoric frames political elites as opportunists. Overall, Dirty Vote emphasizes election fraud as a serious threat to democracy, while encouraging active public involvement in monitoring elections to ensure they remain clean and transparent. Penelitian ini bertujuan untuk menganalisis framing pemilu 2024 dalam film dokumenter Dirty Vote dengan pendekatan kualitatif deskriptif menggunakan model Pan dan Kosicki. Model ini mencakup empat struktur, sintaksis, skrip, tematik, dan retoris. Hasil menunjukkan bahwa Dirty Vote membingkai kecurangan pemilu sebagai ancaman besar bagi demokrasi, dengan menggambarkan manipulasi oleh elite politik sebagai strategi terstruktur. Struktur sintaksis menyoroti peran elite politik, skrip menampilkan manipulasi melalui penunjukan pejabat tidak netral dan politisasi bantuan sosial, tematik memperlihatkan ancaman terhadap keadilan, dan retoris membingkai elite politik sebagai oportunis. Secara keseluruhan, Dirty Vote menekankan kecurangan pemilu sebagai ancaman serius bagi demokrasi, sekaligus mengajak peran aktif masyarakat dalam mengawasi pemilu agar bersih dan transparan.